La faute de la fatalité. Dispositivi romanzeschi di controllo, predestinazione ed eversione - Viscardi, Marco (Status Quaestionis, 2013)
This article analyses two aspects of the complex relationship between providence and coincidence in early nineteenth century European novels. In the first section I will deal with different occurrences of providence in novel plotting, while in the second section, which will be mainly focused on Sternian and comic literature, I will discuss the impossibility of living a random and unpredictable life in nineteenth-century bourgeois society.